Reconstruction of an Ordovician seafloor volcanohydrothermal system: a case study from the Copper Coast, southeastern Ireland using field, geochemical and fluid inclusion data. (2nd January 2018) - Breheny, C.; Moore, K. R.; Costanzo, A.; Feely, M.
Abstract: Volcanic rocks in south County Waterford include flow-top hyaloclastite, pillow lavas and peperite, which are formed typically by sub-aqueous eruption or intrusion into unconsolidated sediment. Element mobility in wet sediment during emplacement of volcanic intrusions was reconstructed on a variety of spatial scales using bulk-rock and mineral analysis. Magma-sediment and magma-water interactions enhanced hydrothermal alteration. The chemistry of chlorite was a function of mixing between an Fe-rich magmatic fluid and a Mg-rich meteoric fluid. Chlorite geothermometry yields temperatures of formation between 230 and 388°C compatible with other metamorphic indicators. Fluid inclusion microthermometric data from genetically-related mineralized quartz veins reveal a hydrothermal vein mineralization event that occurred at lower temperatures during the end stage of volcanic activity. A convection driven mixing trend reflects the trapping of co-existing brine with entrained seawater concomitant with, the late stages of emplacement of the Bunmahon Volcano intrusions.